Teacher Education and Indigenous Knowledge Systems: Integrating Traditional Wisdom into Modern Pedagogy - Joshi Rajkumar Harkishan (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research explores the integration of Indigenous Knowledge Systems (IKS) into modern teacher education to foster culturally responsive pedagogy and sustainable learning practices. Indigenous Knowledge, rooted in generations of experience and cultural heritage, holds immense potential to enrich teaching methodologies by emphasizing community-centered, ecological, and experiential learning. The study examines current teacher education frameworks, identifies gaps in addressing cultural diversity, and analysis successful models of IKS integration globally. Findings highlight the benefits of incorporating IKS, including enhanced cultural sensitivity, inclusivity, and the promotion of ethical and sustainable educational practices. Key recommendations include developing IKS-centered curricula, providing specialized teacher training, and fostering collaboration between educators and Indigenous communities. This research underscores the need for policy reform and institutional support to ensure the effective integration of traditional wisdom into modern pedagogy.
Keywords: Indigenous Knowledge Systems; Teacher Education; Culturally Responsive Pedagogy; Traditional Wisdom; Sustainable Education; Inclusivity; Experiential Learning